2020
DOI: 10.1002/ccd.29453
|View full text |Cite
|
Sign up to set email alerts
|

Safety of same‐day discharge after uncomplicated, minimalist transcatheter aortic valve replacement in the COVID‐19 era

Abstract: Objectives We sought to evaluate the safety, efficacy and feasibility of same‐day discharge after uncomplicated, minimalist TAVR. Background At the start of the COVID‐19 pandemic, we created a same‐day discharge (SDD) pathway after conscious sedation, transfemoral (minimalist) TAVR to help minimize risk of viral transmission and conserve hospital resources. Studies support that next‐day discharge (NDD) for carefully selected patients following minimalist TAVR is safe and feasible. There is a paucity of data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…Observational data show this strategy is safe in cases with a minimalist and uncomplicated approach. 15,16 Indirectly, these data reinforce the results of our analysis, since valve replacement is a more complex procedure from a technical and clinical standpoint, and even in the face of increased complexity, such a strategy proved to be safe.…”
Section: Discussionsupporting
confidence: 81%
“…Observational data show this strategy is safe in cases with a minimalist and uncomplicated approach. 15,16 Indirectly, these data reinforce the results of our analysis, since valve replacement is a more complex procedure from a technical and clinical standpoint, and even in the face of increased complexity, such a strategy proved to be safe.…”
Section: Discussionsupporting
confidence: 81%
“…Specht et al developed a pathway to perform mastectomy with immediate breast reconstruction as a same day procedure, with no resulting readmissions or emergency room visits in eligible patients( 11 ). Similarly, Perdoncin et al reported safe use of same day discharge after transcatheter aortic valve replacement( 12 ) and Abaza et al reported a 98 % same day discharge rate for robotic urologic procedures in response to the pandemic, up from 52 % pre-pandemic( 13 ). One of the unforeseen benefits of the pandemic may be an acceleration of the need to challenge established patterns of post-operative observation and inpatient admission in selected specialties.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the prolonged influence of COVID-19 has led to the extension of the SDD strategy to patients undergoing even more sophisticated procedures, such as transcatheter aortic valve replacement. 13 …”
Section: Discussionmentioning
confidence: 99%